Aging Perception Towards Appearance And Products Satisfaction - Jamalludin, Nurazlina; Majid, Ahmad Zuhairi Abdul; Dolah, Jasni; Noor, Mohamad Najib Mat (2016)
The purpose of this paper is to provide an overview of existing literature on product appearance and the ageing as a consumer. It also examines the relationship between ageing perception towards product appearance in order to better understand how they will respond to products as they grow older. A general literature review was conducted in an effort to identify the significant, substantive work to date. The collected data in this paper were collected from secondary research method. Finally, suggestions are made as a way forward to identify the product appearance attributes and where can be considered by designers, marketers or researchers in designing a product for an ageing population. With the availability of this study, researchers or the designers, thereby can produce a quality and better product design requirements that meet the consumer needs. There is a need to study the ageing and the relationship to product development, specifically in the appearance of the product. By understanding the needs of aging will be beneficial to marketers and designers, especially in designing a product that will fulfil their needs